Dysregulated transmethylation leading to hepatocellular carcinoma compromises redox homeostasis and glucose formation - Curtis C. Hughey; Freyja D. James; Zhizhang Wang; Mickael Goelzer; David H. Wasserman (Elsevier, 2019)
Objective: The loss of liver glycine N-methyltransferase (GNMT) promotes liver steatosis and the transition to hepatocellular carcinoma (HCC). Previous work showed endogenous glucose production is reduced in GNMT-null mice with gluconeogenic precursors being used in alternative biosynthetic pathways that utilize methyl donors and are linked to tumorigenesis. This metabolic programming occurs before the appearance of HCC in GNMT-null mice. The metabolic physiology that sustains liver tumor formation in GNMT-null mice is unknown. The studies presented here tested the hypothesis that nutrient flux pivots from glucose production to pathways that incorporate and metabolize methyl groups in GNMT-null mice with HCC. Methods: 2H/13C metabolic flux analysis was performed in conscious, unrestrained mice lacking GNMT to quantify glucose formation and associated nutrient fluxes. Molecular analyses of livers from mice lacking GNMT including metabolomic, immunoblotting, and immunochemistry were completed to fully interpret the nutrient fluxes. Results: GNMT knockout (KO) mice showed lower blood glucose that was accompanied by a reduction in liver glycogenolysis and gluconeogenesis. NAD+ was lower and the NAD(P)H-to-NAD(P)+ ratio was higher in livers of KO mice. Indices of NAD+ synthesis and catabolism, pentose phosphate pathway flux, and glutathione synthesis were dysregulated in KO mice. Conclusion: Glucose precursor flux away from glucose formation towards pathways that regulate redox status increase in the liver. Moreover, synthesis and scavenging of NAD+ are both impaired resulting in reduced concentrations. This metabolic program blunts an increase in methyl donor availability, however, biosynthetic pathways underlying HCC are activated. Keywords: Intermediary metabolism, Metabolic flux analysis, NAD+, Redox state, S-adenosylmethionine